PENERAPAN PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) DISERTAI LEMBAR KERJA SISWA (LKS) TERHADAP HASIL BELAJAR BIOLOGI SISWA KELAS VII SMP NEGERI 34 SIJUNJUNG - Yegi, Akri - (Pendidikan Biologi, 2014)
The teacher needs to understand learning model in order to the teacher uses variation method. The effort is done by the teacher in problem solving that use cooperative learning type of Think Pair Share (TPS) with the students worksheet (LKS) is the students is give opportunity to think, discuss and share in group discussion. The purpose of the research is to know the studentsâ score at class VII SMP Negeri 34 Sijunjung after applying cooperative learning type of Think Pair Share (TPS) with the studentsâ worksheet (LKS). This research is experiments research with Randomized Control â Group Posttest Only Design. The population of the research is all of the students at class VII SMP Negeri 34 Sijunjung which are registered in two semester year 2013/2014. By using total sampling, in briefly, becoming sample class is VIIA and VIIB. The analysis data uses t test. The result of the research can be got that experiment class have more high score than control class which is 76.12 and 70.08. from hypothesis test is done that th > tt where th = 1.77 and tt = 1.67 so the hypothesis is accepted. Based on the research can be concluded that applying cooperative learning type of Think Pair Share (TPS) with the students worksheet (LKS) can improve the studentsâ biology score at class VII SMP Negeri 34 Sijunjung.